ANALISIS MINAT GENERASI MUDA UNTUK MELANJUTKAN PENDIDIKAN KE JENJANG PERGURUAN TINGGI DI DESA RISA, BIMA - Mariani, Mariani; Hermawansyah, Hermawansyah; Indriani, Irma (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2024)
This research aims to analyze the limited interest of the generation to continue their education to tertiary level in Risa Village, Woha subdistrict. There are 2 main problems in this research; 1) How limited is the generation's interest in continuing their education to tertiary level? 2) What is the solution to overcome the limited interest of the generation to continue their education to tertiary level? This research uses a qualitative research method using a phenomenological approach. The research subjects were the head of Risa Village, RT head, parents, teenagers. Data collection was carried out through observation, interviews and documentation. Data analysis techniques are carried out through several stages 1) data management. 2) Presentation of data. 3) Drawing conclusions. Judging from the research results, it shows that many teenagers are interested in continuing their education to college, but because there are several reasons why many teenagers are unable to continue their education to college. The limited interest of the generation in Risa Village is caused by a social culture that lacks education. Many graduates are unemployed and there are minimal job vacancies. Unhealthy relationships mean that many generations cannot continue their education to college.